THE DEVELOPMENT OF LEARNING ACTIVITIES WITH A PROJECT BASED LEARNING AND DIGITAL LEARNING TOOLS TO PROMOTE THE ENTREPRENEURIAL SKILLS FOR STUDENTS AT GRADE 12 - Suramat, Siraprapa; Kongmanus, Kobsook (Journal of Education and Innovation, 2025)
This research purposes were 1) To develop and improve the quality of academic activities through the framework as a combination of digital learning tools to promote entrepreneurial skills for grade12. 2) To compare pre- and post-knowledge of entrepreneurship. 3) To study entrepreneurial skills. 4) To study satisfaction with the use of digital learning tools, A group of samples include students in grade 12 at the Nongchangwittaya School, Uthaithani province. Thirty-six students were selected by purposive sampling. Research tools include activities plans of Project-Based Learning and Digital learning tools to promote entrepreneurial skills, pretest and posttest, entrepreneurial skills test, and satisfaction questionnaire. The statistics used to analyze the data were percentage, mean, standard division and Non-probability Sampling. The result were concluded as follow: 1) the activities plans of Project-Based Learning and Digital tools to promote entrepreneurial skills have five steps: 1) Define 2) Plan 3) Do 4) Review 5) Presentation and the quality of activities plans of Project-Based Learning and Digital tools to promote entrepreneurial skills were most suitable on highest level ( = 4.72, SD = 0.31) 2) students in grade 12 had posttest scores statistical significant at .05 level higher than pretest scores. 3) the overall entrepreneurial skills are at a very good level, with 80.47 percent passing the criteria. 4) the satisfaction of students in grade 12 after studied towards activities plans of Project-Based Learning and Digital tools to promote entrepreneurial skills were totally highest level ( = 4.71, SD = 0.35).